Energy Absorption Optimization of Multiaction Plastic Working Element of Vehicle Systems under Emergency Impact Loading Conditions - Boiko, A. (Проблемы прочности, 2002)
The aim of this work is to optimize the geometric form of additional plastic working elements of shock absorbers for various cases of impact loading. A finite element model of plastic element was used to evaluate the stressed state generated in cases of coupling of heavy freight trains with various types of mandrel. Numerical simulation results show that application of plastic working element with convex generating line of mandrel is optimal for damping shock loads and minimize damage during collisions.